COMMUNITY SERVICE EDUCATION OF PREGNANT WOMEN IN BATAK CULTURE-BASED HIGH-RISK SCREENING IN MEDAN TUNTUNGAN DISTRICT - Lenny Sepriani Br. Silalahi; Willhelmina Wahara; Elvyana Saragih (Cattleya Darmaya Fortuna, 2024)
High-risk pregnancies require proper early detection to prevent complications that can harm both mother and fetus. In the Batak community in Medan Tuntungan District, there are still challenges in aligning traditional cultural practices with modern medical procedures related to high-risk pregnancy screening. This community service activity aims to increase the knowledge and awareness of pregnant women about the importance of high-risk screening based on an educational Batak cultural approach. The program was carried out on March 15, 2024 through interactive counseling methods, early detection demonstrations, and discussions on local wisdom in safe pregnancy care. The results of the evaluation showed a significant improvement in participants' understanding of pregnancy hazards and the importance of routine check-ups according to medical standards. This education is expected to encourage pregnant women to be more proactive in conducting high-risk screening, so that pregnancy complications can be identified and handled early optimally.